On the normality of giant components. Issue 4 (25th October 2012) - Seierstad, Taral Guldahl
Abstract We consider a general family of random graph processes, which begin with an empty graph, and where at every step an edge is added at random according to some rule. We show that when certain general conditions are satisfied, the order of the giant component tends to a normal distribution. © 2012 Wiley Periodicals, Inc. Random Struct. Alg., 43, 452–485, 2013